Patient preferences for topical treatment of actinic keratoses: a discrete‐choice experiment. (1st April 2019) - Kopasker, D.; Kwiatkowski, A.; Matin, R.N.; Harwood, C.A.; Ismail, F.; Lear, J.T.; Thomson, J.; Hasan, Z.; Wali, G.N.; Milligan, A.; Crawford, L.; Ahmed, I.; et al.
Summary: Background: The treatment of actinic keratosis (AK) is a potentially effective strategy for the prevention of cutaneous squamous cell carcinoma (cSCC). However, the patient perspective on potential benefits of AK treatment in terms of skin cancer reduction has received little attention to date. Objectives: (i) To investigate patient preferences for topical treatments for AK using a discrete‐choice experiment (DCE); (ii) to evaluate patient willingness to trade between clinical benefit and medical burden. Methods: The DCE was conducted as part of a study to establish the feasibility of a phase III randomized controlled trial evaluating the prevention of cSCC using currently available topical interventions. Preferences were elicited by asking patients to make a series of choices between treatment alternatives with different hypothetical combinations of attribute levels. Willingness to trade between treatment attributes was estimated using a flexible‐choice model that allows for the heterogeneity of patient preferences. Results: A total of 109 patients with AK completed the DCE. The majority of patients who expressed valid preferences were willing to accept some reduction in both prophylactic and cosmetic efficacy to reduce the burden of the treatment regimen, the severity of skin reaction and other adverse effects. Patients may reject treatment if the perceived therapeutic benefit is outweighed by the subjective burden of treatment. Conclusions: Evidence of significant variation in the perceived utility of treatments across patients highlights the importance of taking individual patient preferences into account to improve AK treatment acceptability and adherence.